2018
DOI: 10.1002/bmc.4366
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous TLC–densitometric determination of tamoxifen citrate and medroxyprogesterone acetate and UV‐degradation kinetic study of medroxyprogesterone acetate

Abstract: Coadministration of tamoxifen citrate (TMC) and medroxyprogesterone acetate (MPA) is preferred to increase the response rate and the percentage recovery in patients with endometrial carcinoma. Administration of TMC and MPA and their combination affects estrogen and progestin receptor concentrations in advanced endometrium carcinoma by affecting 17β-hydroxyl steroid dehydrogenase activity and serum hormone concentrations. A sensitive, accurate and robust thin-layer chromatography method has been established for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“… 3 Unfortunately, some major side effects, including thromboembolic diseases and endometrial cancer, have limited the use of TAM in healthy women. 6 Severe side effects of TAM are known as its proliferative effect on the endometrium, which is dose-dependent. This reveals that TAM formulation and lower TAM dose with colloidal delivery systems are influential factors for long-term breast cancer chemoprevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Unfortunately, some major side effects, including thromboembolic diseases and endometrial cancer, have limited the use of TAM in healthy women. 6 Severe side effects of TAM are known as its proliferative effect on the endometrium, which is dose-dependent. This reveals that TAM formulation and lower TAM dose with colloidal delivery systems are influential factors for long-term breast cancer chemoprevention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these complex compounds cannot bind to the receptor sites in chromatin and can block estrogen action in the uterus and the breast . Unfortunately, some major side effects, including thromboembolic diseases and endometrial cancer, have limited the use of TAM in healthy women . Severe side effects of TAM are known as its proliferative effect on the endometrium, which is dose-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding chromatography methods, such as liquid, gas, thin layer, and micellar chromatography combined with different detection systems, a number of analytical techniques have been implemented for separating and quantifying TAM and its metabolites [9][10][11][12][13]. Since these compounds are nonvolatile, the use of GC to analyze them requires a derivation step that is extremely time consuming, does not meet the principles of green chemistry, and has not been well received by researchers [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they have a high capability for blocking the action of estrogen in the uterus and the breast [1] . The use of this drug in healthy women has been limited by side effects, such as thromboembolic diseases [9] . One of the dose‐dependent side effects of TAM is its proliferative endometrium effect.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The use of this drug in healthy women has been limited by side effects, such as thromboembolic diseases. [9] One of the dose-dependent side effects of TAM is its proliferative endometrium effect. TAM formulation has confirmed that its lower dose with colloidal delivery systems is an influencing factor for long-term chemoprevention of breast cancer.…”
Section: Introductionmentioning
confidence: 99%